AKR1C1 interacts with STAT3 to increase intracellular glutathione and confers resistance to oxaliplatin in colorectal cancer - Zhiwen Fu; Tingting Wu; Chen Gao; Lulu Wang; Yu Zhang; Chen Shi (Acta Pharmaceutica Sinica B)
Oxaliplatin (OXA), a platinum-based chemotherapeutic agent, remains a mainstay in first-line treatments for advanced colorectal cancer (CRC). However, the eventual development of OXA resistance represents a significant clinical challenge. In the present study, we demonstrate that the aldo-keto reductase 1C1 (AKR1C1) is overexpressed in CRC cells upon acquisition of OXA resistance, evident in OXA-resistant CRC cell lines. We employed genetic silencing and pharmacological inhibition strategies to establish that suppression of AKR1C1 restores OXA sensitivity. Mechanistically, AKR1C1 interacts with and activates the transcription factor STAT3, which upregulates the glutamate transporter EAAT3, thereby elevating intracellular glutathione levels and conferring OXA resistance. Alantolactone, a potent natural product inhibitor of AKR1C1, effectively reverses this chemoresistance, restricting the growth of OXA-resistant CRC cells both in vitro and in vivo. Our findings uncover a critical AKR1C1-dependent mechanism behind OXA resistance and propose a promising combinatorial therapeutic strategy to overcome this resistance in CRC.